What Influences Participation in Non-formal and Informal Modes of Continuous Vocational Education and Training? An Analysis of Individual and Institutional Influencing Factors - Lischewski, Julia; Seeber, Susan; Wuttke, Eveline; Rosemann, Therese (Frontiers in Psychology, 2020)
Participation in further education is a central success factor for economic growth and socie-tal as well as individual development. This is especially true today because in most industri-alized countries, labor markets and work processes are changing rapidly. Data on further education, however, show that not everybody participates and that different social groups participate to different degrees. Activities in continuous vocational education and training (CVET) are mainly differentiated as formal, nonformal and informal CVET, whereby further differences between offers of nonformal and informal CVET are seldom elaborated. Fur-thermore, reasons for participation or non-participation are often neglected. In this study, we therefore analyze and compare predictors for participation in both forms of CVET, name-ly, non-formal and informal. To learn more about the reasons for participation, we focus on the individual perspective of employees (personal characteristics, socialization, job-related factors, learning biography) and integrate institutional characteristics (workplace character-istics and company-based characteristics). The results mainly show that nonformal CVET is still strongly influenced by institutional settings. In the case of informal CVET, on the other hand, the learning biography plays a central role.